A Complex Molecular Interplay of Auxin and Ethylene Signaling Pathways Is Involved in Arabidopsis Growth Promotion by Burkholderia phytofirmans PsJN - Poupin, María J.; Greve, Macarena; Carmona, Vicente; Pinedo, Ignacio (Frontiers in Plant Science, 2016)
Modulation of phytohormones homeostasis is one of the proposed mechanisms to explain plant growth promotion induced by beneficial rhizobacteria (PGPR). However, there is still limited knowledge about the molecular signals and pathways underlying these beneficial interactions. Even less is known concerning the interplay between phytohormones in plants inoculated with PGPR. Auxin and ethylene are crucial hormones in the control of plant growth and development, and recent studies report an important and complex crosstalk between them in the regulation of different plant developmental processes. The objective of this work was to study the role of both hormones in the growth promotion of Arabidopsis thaliana plants induced by the well-known PGPR Burkholderia phytofirmans PsJN. For this, the spatiotemporal expression patterns of several genes related to auxin biosynthesis, perception and response and ethylene biosynthesis were studied, finding that most of these genes showed specific transcriptional regulations after inoculation in roots and shoots. PsJN-growth promotion was not observed in Arabidopsis mutants with an impaired ethylene (ein2-1) or auxin (axr1-5) signaling. Even, PsJN did not promote growth in an ethylene overproducer (eto2), indicating that a fine regulation of both hormones signaling and homeostasis is necessary to induce growth of the aerial and root tissues. Auxin polar transport is also involved in growth promotion, since PsJN did not promote primary root growth in the pin2 mutant or under chemical inhibition of transport in wild type plants. Finally, a key role for ethylene biosynthesis was found in the PsJN-mediated increase in root hair number. These results not only give new insights of PGPR regulation of plant growth but also are also useful to understand key aspects of Arabidopsis growth control.